Vocational education beyond skill formation : VET between civic, industrial and market tensions - Marhuenda-Fluixá, Fernando [Herausgeber] (Peter Lang, 2017)
"Vocational education and training has played an important role in the struggles between Work and Capital along history and today; there are examples of such tensions worldwide. The first section of this book provides illustrations of different countries from the 18th to the early 20th century. The authors explain and exemplify the education of the workforce and its political engagement, contributing to the formation of the working class. The chapters provide relevant approaches to how young apprentices and adult workers developed a class consciousness through vocational education. The second section illustrates practices of resistance and transformation within policies and practices of vocational education nowadays in Central and Southern Europe and South America, addressing the needs of people with disabilities and dispossessed populations. The final section analyses how theories and policies intertwine resulting in the idiosyncrasy of vocational education practices across the world, through tensions between logics and institutional actors. The book addresses the political dimensions of Vocational Education and problematizes its mere consideration as an instrumental tool in skill formation." (Publisher, BIBB-Doku)
Keywords: G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; I 2.2.1 Westeuropa; I 2.3.2 Nordamerika; I 2.3.3 Lateinamerika; Berufsbildung; Historische Entwicklung; Arbeiterklasse; Arbeiterbewusstsein; Arbeiterbildung; 19. Jahrhundert; 20. Jahrhundert; Schweiz; Dänemark; USA; Spanien; Griechenland; Brasilien; Ecuador; Kanada